EAST JAVA BAZNAS AND THE EMPOWERMENT OF PONOROGO’S DISABILITIES COMMUNITY - Zahratul Hayati Utomo; A. Syifaul Qulub (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to find out how the East Java BAZNAS is in the empowerment of disability communities in Sidoharjo Village, Jambon District, Ponorogo, East Java, and to look at the problems that exist to find a solution together. The descriptive qualitative approach with the case study method is the research method used. Using interviews with informants, namely, people who are trusted by BAZNAS to distribute and monitor what is needed by the community and he is also an officer of the Kesra sub-district in Sidoharjo Village. The secondary data comes from journal articles, textbooks and other literature. The results of the study were that the BAZNAS program was very instrumental in helping the community in Sidoharjo Village. Assistance is given aiming to empower people with disabilities; in reality, it fails in the middle of the road. For this reason, community participation is needed considering that human resources are vital to assist them because they can still be empowered as long as they are patient, especially those with mild and moderate disabilities.Keywords: East Java Baznas, Community Empowerment, Disabled Persons, Disability Community EmpowermentREFFERENCE Kementerian Agama RI. (2011). Fiqh Zakat. Surabaya: Bidang Haji Zakat dan Wakaf Kementerian Agama Wilayah Jatim.Presiden Republik Indonesia.  Undang-Undang Republik Indonesia Nomor 8 Tahun 2016 Tentang Penyandang Disabilitas.Republik Indonesia. Undang-Undang Republik Indonesia Nomor 19 Tahun 2011 Tentang Pengesahan Convention On The Rights Of  Persons WithDisabilities (Konvensi Mengenai  Hak-Hak Penyandang Disabilitas).Keputusan Presiden Republik Indonesia Nomor 8 Tahun 2001 Tentang Badan Amil Zakat Nasional Presiden Republik Indonesia.Republik Indonesia. Undang-Undang Republik Indonesia Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat.Daftar Isian Data Dasar Profil Desa Sidoharjo Kecamatan Jambon Kabupaten Ponorogo Tahun 2013.Lilis Nurhidayati. (2016). Gambaran Pelayanan Kesehatan Bagi Penyandang Disabilitas Intelektual Di Wilayah Kerja Puskesmas Jambon Kabupaten Ponorogo. Skripsi tidak diterbitkan. Semarang: Universitas Negeri Semarang.Lin, A.B., Karen, S.M., & Jennifer, E.Y. (2012). Virtue theory and organizations: considering persons with disabilities. Journal of Managerial Psychology, 27(4), 330-346.Hadi, Agus Purbathin. (2004). Konsep pemberdayaan, partisipasi dan kelembagaan dalam pembangunan.Yayasan Agribisnis/Pusat Pengembangan Masyarakat Agrikarya (PPMA).Sugiyono. (2010). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta.Yin, Robert K. (2012). Studi kasus: Desain dan metode. Jakarta: PT Raja Grafindo Persada.Yoghi Citra Pratama. (2015). Peran zakat dalam penanggulangan kemiskinan (studi kasus: program zakat produktif pada Badan Amil Zakat Nasional).  The Journal of Tauhidinomics, 1(1), 93-104.